2019
DOI: 10.1111/1747-0080.12540
|View full text |Cite
|
Sign up to set email alerts
|

Association between sitting time and obesity: A population‐based study in Peru

Abstract: Aim To assess if there is an association between sitting time and obesity among adult Peruvian population, using three different anthropometric measurements. Methods A secondary analysis using data from a population‐based study, the National Household Survey (ENAHO, in Spanish), was conducted enrolling adults aged ≥18 years from the 25 regions of Peru using a multistage random sampling technique. The outcome of interest was obesity, determined by body mass index (BMI > 30 kg/m2), waist circumference (WC > 80 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The influences of the in utero environment on the epigenetic response; changes to the food supply that are rendered by high‐level agricultural, economic and trade policy; improvements in transport and technology that reduce the impetus for physical activity; increases in environmental pollutants potentially influencing cortico‐hypothalamic responses; and, finally, in a world that never seems to darken, disrupting circadian rhythms all contribute to the aetiology of obesity . One example of these effects is highlighted by the article of Paz‐Krumdiek et al, who investigated sedentary behaviour in Peru . Adults spent, on average, nearly 6 hours sitting per day, with nearly one‐quarter of the sample sitting for 8 hours or longer per day.…”
Section: Nutrition As a Complex Sciencementioning
confidence: 99%
“…The influences of the in utero environment on the epigenetic response; changes to the food supply that are rendered by high‐level agricultural, economic and trade policy; improvements in transport and technology that reduce the impetus for physical activity; increases in environmental pollutants potentially influencing cortico‐hypothalamic responses; and, finally, in a world that never seems to darken, disrupting circadian rhythms all contribute to the aetiology of obesity . One example of these effects is highlighted by the article of Paz‐Krumdiek et al, who investigated sedentary behaviour in Peru . Adults spent, on average, nearly 6 hours sitting per day, with nearly one‐quarter of the sample sitting for 8 hours or longer per day.…”
Section: Nutrition As a Complex Sciencementioning
confidence: 99%
“…There are relatively few studies that examined the relationship between different cut-off points of ST with indicators of excess weight (i.e., BMI, WC, and NC) in a large international Latin American sample because of the variety of methodologies applied [ 16 , 17 ]. Only one of these Latin American studies used a representative sample of the urban population.…”
Section: Introductionmentioning
confidence: 99%
“…Paz-Krumdiek et al, found that Peruvian adults with greater ST, using various cut-off points, were more likely to be obese. This association was evident with three different excess weight indicators (i.e., BMI, WC, and waist to height ratio) [ 16 ]. The aim of this study was to verify the association between different cut-points of ST with excess weight, using distinct indicators adjusted for physical activity, in a large adult sample from eight Latin American countries.…”
Section: Introductionmentioning
confidence: 99%
“…This article uses the design of a mobile application for people with overweight problems in Peru with the use of Chatbots, so we can analyze the status of their body mass index of each person, taking into account the percentage of obesity that exists in Peru and decrease with healthy food [7]. To have healthy people using this mobile application with personal data and interacting directly with the use of Chatbots [8].…”
Section: Introductionmentioning
confidence: 99%